Inside the Cell - U.S. Department of Health and Human Services (2005)
RESUMEN Athrough your brain, voracious killers are coursing through your veins, and corrosive chemicals sizzle in bubbles from your head to your toes. In fact, your entire body is like an electrical company, chemical factory, transportation grid, communications network, detoxification facility, hospital, and battlefield all rolled into one. The workers in each of these industries are your cells. Cells are the smallest form of life—the functional and structural units of all living things. Your body contains trillions of cells, organized into more than 200 major types.